Prehospital anaesthesia: a survey of current practice in the UK. Issue 2 (12th March 2011) - Cowan, G M; Burton, F; Newton, A
Abstract : Aim: To establish the national picture of prehospital anaesthesia in the UK and to reference practice against the Association of prior to Anaesthetists of Great Britain and Ireland safety guideline on prehospital anaesthesia. Methods: Lead clinicians were identified for all prehospital services in the UK that could potentially be performing prehospital anaesthesia and invited to complete a detailed online survey. The survey requested details on team structure, the process for prehospital anaesthesia, drugs and equipment used and training and governance arrangements. Results: 55 responses were received from 63 invitations sent (87.3%) yielding usable data for 47 services. 31 of the 47 services (70%) responded that they performed prehospital anaesthesia. All services performing prehospital anaesthesia utilised a doctor but only 18 services (58%) always utilised a trained assistant. 28 services (90%) maintained a database and over half of services (55%) performed less than 20 prehospital anaesthetics annually. 23 services (74%) had a designated lead clinician for prehospital anaesthesia and 25 (81%) had a written difficult airway plan. 19 services (61%) had mandatory continual training requirements. Conclusions: The majority of services are currently complying with the recommendations in the Association of prior to Anaesthetists of Great Britain and Ireland safety guideline. There are still areas of concern, particularly with regard to ongoing training and the high numbers of services that do not use a trained assistant for the process of prehospital anaesthesia.